Heat transfer in the formation - Moradi, B. (Maxwell Science Publications, 2013)
Heat loss from the wellbore fluid depends on the temperature distribution in the formation; since it is necessary to know the formation temperature distribution as a function of radial distance and time for computing the fluid flow temperature in the wellbore. This study solves energy balance equation in the formation by analytical and numerical solutions. Comparison of analytical and numerical solutions results figured out good agreement between those solutions, except early times. This study further showed the temperature changes in small area, only near the wellbore in the formation. Â© Maxwell Scientific Organization, 2013.